Diagnostic role of fine needle aspiration cytology (FNAC) in the evaluation of salivary gland swelling: an institutional experience - Naz, Samreen (BMC Res Notes, 2015)
BACKGROUND: Fine needle aspiration cytology (FNAC) is a cytodiagnostic method based on morphologic findings of individual and small group of cells aspirated using a fine needle. The aim of the present study is to evaluate the spectrum of salivary gland lesions in our setting and to assess the diagnostic accuracy of FNAC for salivary gland lesions. METHODS: The study involved 187 cases of parotid and submandibular swellings of patients who underwent FNAC at our institution. Thirty one (31) patients with a FNAC diagnosis of neoplastic lesion subsequently underwent excision biopsies. The results of FNAC and final histology were compared and accuracy of FNAC was determined. RESULTS: Mean age of patients was 42 (±21) years and male to female ratio was 1:1. Chronic sialadenitis was the most common non-neoplastic lesion (33.8%) followed by acute and chronic sialadenitis (29.7%) and chronic granulomatous inflammation (27.0%). Pleomorphic adenoma was the most common benign neoplasm and non-Hodgkin’s lymphoma was the most common malignant lesion (38.9%) followed by acinic cell (27.8%) and adenoid cystic carcinoma (16.7%). Total 31 patients subsequently underwent surgical excision, out of which 21 were benign and 9 were malignant, 20 cases (64.5%) were of pleomorphic adenoma, 3 cases (9.6%) of acinic cell carcinoma, 2 cases (6.4%) each of warthin tumor, adenoid cystic carcinoma and non-hodgkin lymphoma and 1 case (3.2%) each of mucoepidermoid carcinoma and mucinous adenocarcinoma. The overall accuracy of FNAC in our study was found to be 83.8% with 77.7% sensitivity and 86.3%, specificity. The revised sensitivity and specificity after adjusting verification bias were 68.5% and 91% respectively. False negative diagnosis was rendered in mucoepidermoid carcinoma and acinic cell carcinoma whereas false positive diagnosis was given in cases of pleomorphic adenoma. CONCLUSION: We found a good concordance between FNAC and histology, however pleomorphic adenoma may impart a diagnostic challenge when inadequately aspirated and therefore we advice either immunohistochemical studies (if cell block material is available) or repeat aspiration in difficult cases.